A Holocene marine pollen record from the northern Yenisei Estuary (southeastern Kara Sea, Siberia). - Kraus, Matthias; Matthiessen, Jens; Stein, Ruediger (PANGAEA, 2003)
AMS-14C dated sediment cores from the Ob and Yenisei estuaries and the adjacent inner Kara Sea were investigated to determine the siliclastic and organic carbon fluxes and their relationship to paleoenvironmental changes. The variability of sediment fluxes during Holocene times is related to the post-glacial sea-level rise and changes in river discharge and coastal erosion input. Whereas during the late/middle Holocene most of the terrigenous sediments were deposited in the estuaries and the areas directly off the estuaries, huge amounts of sediments accumulated on the Kara Sea shelf farther north during the early Holocene before about 9 Cal. kyrs. BP. The maximum accumulation at that time is related to the lowered sea level, increased coastal erosion, and increased river discharge due to the final stage of mountain deglaciation of the Putoran Massif. Increased supply of Yenisei-derived material indicated by peak magnetic susceptibility values probably occurred in climate-related pulses culminating near 11, 10, and 9 Cal. kyrs. BP. As sea level rose, the main Holocene depocenter migrated southward. Based on hydrogen index values and n-alkanes, the organic matter is predominantly of terrigenous origin. Maximum accumulation rates of 1.5 to more than 6 g/cm2/y occurred in the early Holocene sediments, suggesting more humid climatic conditions with an increased vegetation cover in the source area at that time. In general, high organic carbon accumulation rates characterize the estuaries and the inner Kara Sea as important sink for terrigenous organic carbon. A high-resolution record of Holocene variability of magnetic susceptibility (MS) in an AMS14C-dated sediment core from the northern Yenisei estuary may indicate natural variability of Arctic climate change and river discharge on a centennial to millenial time scale. Short-term maxima in MS probably related to warmer climate, enhanced precipitation, intensified weathering/erosion and increased river discharge, display a frequency of about 300 to 700 years.
Pollen record and age determination of a sediment core from the Kara Sea
Keywords: Siberian River Run-Off; SIRRO